The Effect Of Individual Character, Organizational Character, And Legal Environment On The Quality Of Financial Statements Of Public Hospital C – Type In The Bengkulu City - Yuli Yusnita; Lismawati Lismawati; Siti Aisyah (Penerbit Jurnal Indonesia, 2025)
This research aims to find how the effect of individual character, organizational character, and legal environment on the quality of financial statement. This research respondents are involved in the financial statement reporting who are of Public Hospital C-Type in the Bengkulu City. The Hypotheses test in this research is using the Multiple Linear regression. The results of these test are all variable influences the Quality Of Finacial Statements. The Hypotheses shown positive significant on all variable toward Quality Of Finacial Statements.